The Platelet Function Analyzer (PFA-100) as a Screening Tool in Neurosurgery. (8th August 2012) - Karger, Ralf; Reuter, Karoline; Rohlfs, Jochen; Nimsky, Christopher; Sure, Ulrich; Kretschmer, Volker
Abstract : We investigated whether the inclusion of the PFA-100 in the preoperative screening of neurosurgical patients might reduce perioperative bleeding complications. Patients with intracranial space-occupying lesions who were scheduled for neurosurgery underwent routine preoperative PFA-100 testing. In case of an abnormal PFA test, patients received prophylactic treatment with desmopressin. 93 consecutive patients were compared to 102 consecutive patients with comparable characteristics operated before introduction of the PFA-100 testing. 2 patients (2.2%) in the PFA group and 2 patients (2.0%) in the non-PFA group experienced clinically relevant intracranial bleeding confirmed by computed tomography (OR 1.05, 95% CI 0.39–2.82; P = 1.0 ). Transfusions were not significantly different between the two groups. 13 (14.0%) patients in the PFA group and 5 (4.9%) patients in the non-PFA group received desmopressin (OR 3.2, 95% CI 1.1–9.2; P = 0.045 ). Preoperative screening with the PFA-100 did result in a significant increase in the administration of desmopressin, which could not reduce perioperative bleeding complications or transfusions.